Boom visions and insights for creating wealth in the 21st century - Vogl, Frank (Irwin Professional Pub., 1996)
"The world's wisest investors and the shrewdest multinational corporations are already positioning themselves to take full advantage of the exploding global market. For investors looking to expand their horizons across the globe, BOOM is the comprehensive outline for the emerging market order, describing the dramatic evolution of global business opportunities at the dawn of a new century." "Finally, the authors - currently in the midst of building a multinational enterprise themselves - outline their own experiences and demonstrate that they practice what they have described throughout the book."--BOOK JACKET.